BAHASA SUBORDINASI PEREMPUAN SASAK - Muttaqin, Zainul (University of Brawijaya, 2020)
The phenomenon of women in the culture of Sasak community is always attached to the inferiority aspect which in this case is subordinated. Not only on aspects that have become public secrets, such as inequality of rights in access to education, employment, and social status, but there are also forms of subordination of Sasak women at the lingual level which has been running hand in hand with the pattern of subordination is commonly done. The theory used to examine this problem is the theory of Teu A Van Djik, Social Cognition. The method used is the method of observation, interviews and notes. The results of this study are found in two schemes that appear, namely the scheme of roles and the scheme of events. The results are 14 data obtained in five (five) villages in Sakra District, East Lombok Regency, NTB.Â